PENATAAN ALUN-ALUN, PASAR DAN HUNIAN SEBAGAI TITIK TEMU KOMUNITAS MASYARAKAT EMPANG KOTA BOGOR - Grace Edria; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2022)
The Empang neighborhood, also known as the Arab Village, is a part of Bogor that is notorious for being a slum and a filthy place to live and conduct business. When describing the region's early development, it should be noted how involved it was in government affairs. Physical degradation such as abandoned towns, disorganized traditional markets, and inoperable squares are some ways that its development has slowed down over time rather than improved. In the city of Bogor, contemporary marketplaces are currently expanding quickly while old markets are falling behind. Concern must be expressed over the decline of enthusiasts, particularly among the current generation of traditional markets. The old market in the Empang neighborhood is seen as being unattractive because it is excessively filthy, stinky, and dirty and because it does not meet modern needs. The Great Mosque of Empang, An Noer Mosque, and Habib Abdullah's Tomb are all nearby historical landmarks, therefore this project has a great deal of potential to engage with the neighborhood as a welcoming location that offers open space for the locals. A plan to reorganize the residential area, commerce, and services of the Empang Area is developed using the Urban Acupuncture approach. With this design, it is intended that the location will once again serve as a hub for the interaction and gathering of the Empang community. The Empang area can become a dynamic, well-organized place and a new face for the Empang area, which has long since lost its identity, through the Urban Acupuncture strategy. Keywords: The Square; Bogor; Dwelling; Empang Area; Market Abstrak Kawasan Empang atau yang biasa disebut dengan kampung Arab merupakan kawasan yang di kenal sebagai kawasan pemukiman serta perdagangan dan jasa yang kumuh dan kotor di Kota Bogor. Dalam paparan sejarah pertumbuhannya, semula kawasan Empang sangat aktif kegiatan pemerintahannya. Seiring berjalannya waktu, perkembangannya tidak menunjukkan ke arah yang lebih baik, namun mengalami penurunan dari berbagai aspek, salah satunya yaitu mengalami degradasi fisik, seperti permukiman yang terbengkalai, pasar tradisional yang berantakan dan alun-alun yang tidak berfungsi. Di masa ini, keberadaan pasar modern di Kota Bogor berkembang pesat sedangkan pasar tradisional semakin tertinggal. Menurunnya peminat peminat khususnya generasi sekarang akan pasar tradisional harus menjadi perhatian. Pasar tradisional Kawasan Empang yang dinilai sudah terlalu kotor, bau, jorok, tidak mengikuti kebutuhan zaman sehingga menjadi tidak lagi menarik. Berlokasi dekat peninggalan bersejarah, Masjid Agung Empang, Masjid An Noer, dan makam Habib Abdullah menjadikan proyek ini sangat potensial untuk dapat berkolerasi dengan lingkungan sekitar sebagai tempat nyaman yang menyediakan area terbuka bagi masyarakat sekitar. Melalui pendekatan urban akupunktur disusun rencana penataan kembali lingkungan hunian, perdagangan dan jasa kawasan Empang. Dengan penataan ini diharapkan kawasan dapat kembali menjadi sebuah titik temu bagi masyarakat Empang untuk berinteraksi dan berkumpul. Melalui pendekatan urban akupunktur kawasan Empang dapat menjadi area yang hidup dan lebih tertata serta mampu menjadi wajah baru untuk Kawasan Empang yang sejak lama kehilangan identitasnya.